2016
DOI: 10.1016/j.ces.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Filtered sub-grid constitutive models for fluidized gas-particle flows constructed from 3-D simulations

Abstract: The accuracy of fluidized-bed CFD predictions using the two-fluid model can be improved significantly, even when using coarse grids, by replacing the microscopic kinetic-theory-based closures with coarsegrained constitutive models. These coarse-grained constitutive relationships, called filtered models, account for the unresolved gas-particle structures (clusters and bubbles) via sub-grid corrections.Following the previous 2-D approaches of Igci et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 27 publications
1
116
0
1
Order By: Relevance
“…For example, constant correlation coefficients are used to close sub-filter variances, e.g., Eq. (16). Applying a dynamic adaption procedure may considerably improve the local predictions of the SA-TFM approach [32].…”
Section: Pilot-scale Fluidized Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, constant correlation coefficients are used to close sub-filter variances, e.g., Eq. (16). Applying a dynamic adaption procedure may considerably improve the local predictions of the SA-TFM approach [32].…”
Section: Pilot-scale Fluidized Bedmentioning
confidence: 99%
“…Nevertheless, such a procedure inevitably neglects the small (unresolved) scales [13,14]. Consequently, many sub-grid drag modifications have been proposed to account for the effect of these small mesoscale structures on the resolved macroscales [2,12,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of efforts have been made to develop and validate mesoscopic (e.g., filtered model) TFM and macroscopic (e.g., averaged model) TFM . Heterogeneous drag development and validation are one of the most critical parts of coarse‐grid simulation and it is the focus of many previous studies .…”
Section: Introductionmentioning
confidence: 99%
“…In many previous studies, reasonably good predictions of the gas–solid flow behavior were reported by employing the standard TFM with only drag correction; other subgrid corrections, such as mesoscale stress, were assumed to be negligible and were not considered. However, some studies reported that the mesoscale stress (subgrid phase stress modeled in the coarse‐grid TFM) is about one‐order magnitude larger than the microscale stress (phase stress appearing in the standard TFM) at least. The neglecting of mesoscale stress will bring large uncertainty and it is needed for coarse‐grid simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation